2021
DOI: 10.3390/su132011384
|View full text |Cite
|
Sign up to set email alerts
|

Psychological and Physical Health of Organic and Conventional Farmers: A Review

Abstract: Farmers’ health compared to the general population has been the object of some studies and reviews. Among all factors implied in psychological and physical health, the farming system (i.e., organic or conventional farming) was identified as one of the relevant factors to investigate. This article aims to review the literature established on the comparison between organic and conventional farmers’ health and its correlates. Twenty-nine quantitative or qualitative articles were identified for inclusion (n = 29).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 46 publications
3
4
0
Order By: Relevance
“…These data were in line with the literature regarding anxiety [26,27] but lack support regarding life satisfaction [26,28], job satisfaction [21,29,30] and wellbeing [31]. In addition, the effect sizes observed correspond to average effects according to Cohen's classification [56], which was in line with what is usually observed in the literature [23]. With regard to the absence of differences in depression, these results were in line with those of Cross et al [24], Khan et al [22], and Nankongnab et al [33].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…These data were in line with the literature regarding anxiety [26,27] but lack support regarding life satisfaction [26,28], job satisfaction [21,29,30] and wellbeing [31]. In addition, the effect sizes observed correspond to average effects according to Cohen's classification [56], which was in line with what is usually observed in the literature [23]. With regard to the absence of differences in depression, these results were in line with those of Cross et al [24], Khan et al [22], and Nankongnab et al [33].…”
Section: Discussionsupporting
confidence: 90%
“…Thus, these data show several differences in the advantage of organic farmers on some dimensions and no difference on other dimensions. Moreover, no dimension showed a trend in favor of conventional farming, in line with the literature [23].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…According to the results of research by Mie et al [18], eating organic food can reduce the risk of allergic diseases as well as overweight and obesity. French research results from David et al [19] showed that farmers working in the organic system have better mental and physical health than those working in the conventional system.…”
Section: Theoretical and Empirical Backgroundmentioning
confidence: 99%